Empathy among Guatemalan adolescents: a mixed-methods study of culture and economic condition - Judith L. Gibbons; Brien K. Ashdown; Katelyn E. Poelker (International Journal of Adolescence and Youth)
Cultural and economic contexts shape adolescents’ socio-emotional development. We conducted an explanatory sequential mixed-methods study of adolescents’ empathy, a component of social development, in two schools in Guatemala, a country marked by collectivism and economic disparity. Participants (N  = 119, ages 12–18, 64 girls) who attended either a school serving low-resource students or one serving affluent students completed the adapted Basic Empathy Scale and reported household amenities. Adolescents from the low-resource school reported more affective and cognitive empathy; household amenities mediated the relation between school and affective empathy. Thematic analysis of daily hassles and sources of gratitude revealed that interpersonal relationships were paramount for students from both schools. Students from the affluent school disdained hypocrisy, sought time alone, and resisted parents’ control. Students from the low-resource school perceived a shared fate and sought attention and respect. The empathy of adolescents living in poverty may be harnessed to promote their empowerment.